PENGARUH EXCHANGE RATE, PDB, DAN HARGA MINYAK MENTAH TERHADAP VOLUME EKSPOR MINYAK MENTAH INDONESIA - Vidiantari Devi1, Made Feninda; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
ABSTRACT The objectives of this study are (1) to analyze the effect of exchange rate, GDP, and crude oil prices simultaneously on the volume of Indonesian crude oil exports and (2) to analyze the effect of exchange rate, GDP, and crude oil prices simultaneously on the volume of Indonesian crude oil exports. . This research was conducted in Indonesia with data on the export of Indonesian crude oil with the total number of data observed was 40 (forty) data. Data collection techniques are non-participant observation techniques. The data analysis technique used multiple linear regression analysis. The results show that the Exchange rate, GDP, and crude oil prices simultaneously affect the volume of crude oil exports. Exchange Rate has a positive and significant effect on the volume of crude oil exports. GDP has a positive and significant effect on the volume of crude oil exports. The price of crude oil has a positive and significant effect on the volume of crude oil exports. Keywords : Exchange Rate, GDP, Crude Oil Price, and Crude Oil Export Volume